Confocal three‐dimensional micro‐X‐ray fluorescence spectroscopy used to retrieve the information covered in printed paper. (25th July 2019) - Sun, Xuepeng; Zhang, Xiaoyun; Wang, Xinyun; Wang, Yabing; Li, Yufei; Peng, Shiqi; Shao, Shangkun; Liu, Zhiguo; Shang, Hongzhong; Sun, Tianxi
Abstract : Confocal three‐dimensional micro‐X‐ray fluorescence (3D‐μXRF) spectroscopy based on laboratory X‐ray tube was employed to unravel the three‐dimensional (3D) distribution of metal element (Fe) inner the paper. According the distribution of the Fe in the paper, the information covered in the printed paper could be retrieved. Before the experiment, the performance of the confocal 3D‐μXRF setup was described. The two‐dimensional (2D) mapping of printed character covered by the opaque tape and contaminated by the black ink was scanned by confocal 3D‐μXRF setup. Furthermore, 2D and 3D mapping of a printed number covered by the paper with printed character was performed by micro‐X‐ray fluorescence and confocal 3D‐μXRF setup, respectively. The scanning results indicated that confocal 3D‐μXRF was more suitable for retrieving the information covered in the paper. Furthermore, the confocal 3D‐μXRF setup has potential application on the identification of unseen letter or painting that was covered by others, such as ink.